Genetic Polymorphisms in the Dopamine Receptor 2 Predict Acute Pain Severity After Motor Vehicle Collision. Issue 9 (September 2015) - Qadri, Yawar J.; Bortsov, Andrey V.; Orrey, Danielle C.; Swor, Robert A.; Peak, David A.; Jones, Jeffrey S.; Rathlev, Niels K.; Lee, David C.; Domeier, Robert M.; Hendry, Phyllis L.; Mclean, Samuel A.
<x xml:space="preserve">Abstract</x> Objectives: Dopaminergic signaling is implicated in nociceptive pathways. These effects are mediated largely through dopamine receptors and modulated in part by dopamine transporters. This study tested the hypothesis that genetic variants in the genes encoding dopamine receptor 2 (DRD2) and the dopamine active transporter (SLC6A3) influence acute pain severity after motor vehicle collision. Materials and Methods: European Americans presenting to the emergency department after motor vehicle collision were recruited. Overall pain intensity in emergency department was assessed using a 0 to 10 numeric rating scale. DNA was extracted from blood samples and genotyping of single-nucleotide polymorphisms (SNPs) in the DRD2 and SLC6A3 gene was performed. Results: A total of 948 patients completed evaluation. After correction for multiple comparisons, SNP rs6276 at DRD2 showed significant association with pain scores, with individuals with the A/A genotype reporting lower mean pain scores (5.3; 95% confidence interval [CI], 5.1-5.5) than those with A/G (5.9; 95% CI, 5.6-6.1) or G/G (5.7; 95% CI, 5.2-6.2) genotypes (P=0.0027). Secondary analyses revealed an interaction between sex and DRD2 SNPs rs4586205 and rs4648318 on pain scores: females with 2 minor alleles had increased pain intensity, whereas males with 2 minor alleles had less pain than individuals with a major allele (interaction P=0.0019). Discussion: Genetic variants in DRD2 are associated with acute pain after a traumatic stressful event. These results suggest that dopaminergic agents may be useful for the treatment of individuals with acute posttraumatic pain as part of a multimodal opioid-sparing analgesic regimen.